(untitled) (Research, Society and Development, 2022)
This study aims to reflect on the finding of the literature on the Humanistic Theory in palliative care. This in an integrative review, carried out in the Scielo, PubMed, LILACS, Nursing Database (BDENF), Virtual Health Library (BVS), Scopus and Web of Science, databases from April to May 2022. The research question was: “What scientific evidence, in the contexto of humanistic theory, is available about patients in palliative care?” A total of 22.814 studies were found, and after analysis, five studies were included in this work. Among the analyzed studies, it is observed that three of them are is English, one in Portuguese and one in Spanish. Regarding the year of publication, one was published in 2007, one in 2013, one in 2017, one in 2019 and one in 2020. The main findings in the literature on the humanistic theory in relation to patients en palliative care concern care individuality and Humanistic Theories of Travelbee and Paterson and Zederad. The present study showed thet the humanistic theory in relation to patients in palliative care provides the maintenance of the quality of life, dignity and autonomy of these patients in their final stage of live. However, future studies with a better level of evidence are necessary since studies on Humanistic Theory in palliative care are still scarce.